PENGARUH OPINI AUDIT, PERINGKAT KAP, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN AUDITOR SWITCHING SEBAGAI VARIABEL MEDIASI - Sanulika, Aris (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
This research is structured to analyze how Influence of Audit Opinion, Firm Size, Company Size Profitability To Company Value With Switching Auditor As Variable Mediation.The research methodology used using explanatory causality method and using secondary data. Sample selection using purposive sampling method and sample used amounted to 25 companies with rentng time 2008-2014.Based on the result of the audit opinion t test 2,235 with the significance level 0.027 smaller than 0.05. KAP threshold size variable 0.711 with significance level 0,478 greater than 0,05. Variable size of company titung 4,127 with significance level 0,00 less than 0,05. The profitability variable is tcal 4.00 with the significance level 0.00 is less than 0.05. Switcing Auditor Variable tcal -1,892 with 0.061 significance level greater than 0.05. Although the switching auditor directly does not affect the firm's value, the audit opinion variables, KAP size, firm size and profitability to firm value are mediated by the Switching Auditor. The value of the company to increase this means investors' confidence in the company is increasing due to the change of both big four and non big four auditors but the results of his unqualified opinion